Analisis Tingkat Penyebaran Suhu Inkubator Bayi Dengan Sensor DS18B20 - Eko Arianto; Agus Siswoyo (J-Innovation, 2022)
A baby incubator is a special device used by newborns that is used to keep the baby's temperature warm. The temperature in the baby incubator can be adjusted according to the baby's needs. Babies who need the most incubators are babies born prematurely and babies born with low weight. A good baby incubator is one that can maintain the required temperature stably and evenly throughout the room. In this study, we will focus on observing the temperature distribution in the baby incubator. Tests in this study will use a lab-scale baby incubator. The baby incubator will be set at 32℃ then the DS18B20 temperature sensors will be placed on four sides in the baby incubator room. Then measurements will be made for 30 minutes and timed data is taken every 2 minutes. The baby incubator temperature analyzer prototype was successfully made and tested in comparison with several other temperature sensors, the result is that the DS18B20 is stable and can indeed be a good choice of temperature sensor. The results of testing the level of heat distribution in the baby incubator, there is an uneven temperature at each sensor point with a difference of 0.15 ~ 0.29℃. When compared to the Krisbow Environment meter, the Environment measurement results tend to be lower. The results of this analysis indicate that there is an uneven distribution of heat in the incubator <0.30℃. It is necessary to do a more detailed analysis on each incubator temperature setting, namely at a temperature of 32~37℃ in another study.